Analysis of Downtime Problems on Elevator Machine at PT. Santosa Utama Lestari using Tree Diagrams - Mashabai, Ismi; Irahayu Asran, Andi Mustika (SAINTEKBU, 2023)
Downtime is a condition in which the machine stops operating not on scheduled stops but due to a disturbance that occurs on the machine, so the machine will be idle until the machine has been repaired or is not in a state of disturbance. Downtime is when production equipment is not functioning due to a sudden inspection and repair of damaged equipment. Elevators can raise the material to a height of up to 50 meters; the capacity can reach 50 ????3/hour. The construction can reach a vertical position. The working principle of this tool is to move the material vertically by placing the material in buckets which are linked by a chain or belt at a certain distance which rotates on the pulley so that the bouquet can move vertically. This study uses the tree diagram method to analyse downtime problems by applying the 5 M + 1E technique.